Strategic planning as a catalyst for sustainability: A mediated model of strategic intent and formulation in manufacturing SMEs. - Ahmed Muneeb Mehta; Syeeduz Zafar Qazi; Rasheedul Haque; Abdul Rahman Bin S Senathirajah; Waqas Baig; Rabia Sajjad; Dr Abdul Rauf (PLoS ONE)
This study examines the influence of Systematic Strategic Planning (SSP) on the Sustainable Performance (SP) of manufacturing Small and Medium Enterprises (SMEs) in Pakistan. Despite SMEs' vital contribution to economic growth, there is limited empirical research on how strategic planning enhances sustainable performance in SMEs operating in emerging economies facing political and economic instability. Drawing on the Triple Bottom Line (TBL) and Resource-Based View (RBV) theories, this study investigates the mediating roles of Strategic Intent (SI) and Strategic Formulation (SF) in the SSP-SP relationship. A quantitative research design was employed, and data were collected through structured questionnaires distributed to senior executives and decision-makers of manufacturing SMEs. A total of 410 valid responses were received. Structural Equation Modeling (SEM) was applied using AMOS 28 software to analyze the data and test the hypothesized relationships. The results demonstrate that SSP has a significant direct effect on SP and an indirect effect through SI and SF. Specifically, the components of SSP-strategic analysis, strategy creation, strategy execution, and monitoring and evaluation-enhance SMEs' economic, environmental, and social performance. The study highlights that adopting systematic strategic planning practices enables SMEs to navigate complex and uncertain environments, achieve competitive advantage, and contribute to sustainable development goals. This research fills a critical gap in the literature by focusing on manufacturing SMEs in Pakistan, an under-researched context in the sustainability and strategic management fields. It offers practical insights for SME managers and policymakers to develop and implement comprehensive strategic planning frameworks that foster sustainability. The study also provides theoretical contributions by integrating SI and SF as key mediators within the TBL and RBV theoretical frameworks.